Analysis of Total Acidity toward Bacterial and Endophytic Fungi Profile dur-ing Black Garlic Processing from Garlic (Allium sativum L.) and Shallot (Allium ascalonicum L.) - Lestari, Ayu Rahmania; Wonorahardjo, Surjani; Suharti, Suharti (Makara Journal of Science, 2021)
Black garlic or shallot are products of processed garlic and shallots obtained through a heating process conducted over a certain period. Black garlic/shallots have a mild aroma with a sweet and sour taste. The heating process causes chemical compound transition in the garlic, including acidity. In addition to the chemical process, the garlic’s color and component changes are due to the role of microorganisms during black garlic processing. However, the presence and function of such microorganisms have not been identified. Therefore, this research explores the black garlic’s microorganisms, their role in black garlic processing, and their relation to the total acidity changes. Total acidity test was completed using the potentiometric titration method, while the onion’s microorganisms were explored through isolation and characterization. Data show that black garlic’s total acidity of both garlic and shallot increases during the heating period day by day. Endophytic microbes that were successfully isolated during black garlic processing were observed on days 0 and 6. According to the rough data, the bacteria that emerged on day 0 are presumed to come from genus Erwinia, Pseudomonas, Xanthomonas, Agrobacterium, Ralstonia, Xylophilus, Pantoea, Acidovorax, Burkholderia, Coryneform, and Streptomyces, while the bacteria observed on day 6 are assumed to be generated from genus Coryneform and Streptomyces.